Immobilizing lead and copper in aqueous solution using microbial- and enzyme-induced carbonate precipitation - Wang, Lin; Cheng, Wen-Chieh; Xue, Zhong-Fei; Rahman, Md Mizanur; Xie, Yi-Xin; Hu, Wenle (Frontiers in Bioengineering and Biotechnology, 2023)
Inappropriate irrigation could trigger migration of heavy metals into surrounding environments, causing their accumulation and a serious threat to human central nervous system. Traditional site remediation technologies are criticized because they are time-consuming and featured with high risk of secondary pollution. In the past few years, the microbial-induced carbonate precipitation (MICP) is considered as an alternative to traditional technologies due to its easy maneuverability. The enzyme-induced carbonate precipitate (EICP) has attracted attention because bacterial cultivation is not required prior to catalyzing urea hydrolysis. This study compared the performance of lead (Pb) and copper (Cu) remediation using MICP and EICP respectively. The effect of the degree of urea hydrolysis, mass and species of carbonate precipitation, and chemical and thermodynamic properties of carbonates on the remediation efficiency was investigated. Results indicated that ammonium ion (NH4+) concentration reduced with the increase in lead ion (Pb2+) or copper ion (Cu2+) concentration, and for a given Pb2+ or Cu2+ concentration, it was much higher under MICP than EICP. Further, the remediation efficiency against Cu2+ is approximately zero, which is way below that against Pb2+ (approximately 100%). The Cu2+ toxicity denatured and even inactivated the urease, reducing the degree of urea hydrolysis and the remediation efficiency. Moreover, the reduction in the remediation efficiency against Pb2+ and Cu2+ appeared to be due to the precipitations of cotunnite and atacamite respectively. Their chemical and thermodynamic properties were not as good as calcite, cerussite, phosgenite, and malachite. The findings shed light on the underlying mechanism affecting the remediation efficiency against Pb2+ and Cu2+.